2022
DOI: 10.1177/00034894211070132
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Type 1 Thyroplasty Versus Injection Laryngoplasty for Vocal Fold Movement Impairment After Extent type I and II Aortic Repair

Abstract: Importance: Vocal fold motion impairment (VFMI) due to neuronal injury is a known complication following thoracic aortic repair that can impair pulmonary toilet function and post-operative recovery. Objective: To demonstrate clinical outcomes of patients undergoing inpatient vocal fold medialization for VFMI after aortic surgery. Design: A 15-year retrospective chart review (2005-2019) of 259 patients with postoperative VFMI after thoracic aortic surgery registry was conducted. Data included demographics, surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…One similar instance of complication overreporting was conducted by Pinzas et al where they analyzed MT following thoracic aortic surgery 57 . The researchers reported that 36 of 126 total patients (28.6%) experienced pulmonary toilet related complications, including 17 cases of reintubation and 14 tracheostomies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…One similar instance of complication overreporting was conducted by Pinzas et al where they analyzed MT following thoracic aortic surgery 57 . The researchers reported that 36 of 126 total patients (28.6%) experienced pulmonary toilet related complications, including 17 cases of reintubation and 14 tracheostomies.…”
Section: Discussionmentioning
confidence: 80%
“…12 One similar instance of complication overreporting was conducted by Pinzas et al where they analyzed MT following thoracic aortic surgery. 57 The researchers reported that 36 of 126 total patients (28.6%) experienced pulmonary toilet related complications, including 17 cases of reintubation and 14 tracheostomies. This report is somewhat misleading, as the MTs were conducted, on average, 8 days following thoracic aortic surgery, a procedure where pulmonary toilet-related complications occur at rates as high as 45%-48%.…”
Section: Complicationsmentioning
confidence: 99%